Improving access to maternal health care beyond health care policy: pregnant women's experience of maternal public health care services in Cape Town, South Africa - Rhoda, Bronwin (Department of Environmental and Geographical Science, 2024)
Unequal access to maternal health care continues to be a concern in South Africa despite the efforts of government and health practitioners to make the system more inclusive and accessible to all women, especially for women who have been previously disadvantaged prior to and during Apartheid. Research in maternal health care has shifted and emphasized the delivery of quality care by medical staff to ensure that the goal of reducing maternal deaths is to improve maternal health care. Despite the global concern and interventions of the local government, many women still experience limited access to quality maternal healthcare services. Waiting for public health care services further highlights women's challenges. There is a need to understand further how waiting impacts the patients' experience and access to care. Acknowledging that gaps exist in the current literature focused on maternal health care, this study employs qualitative research methods to explore pregnant women's experience within the maternal public health care system in the Cape Town Metropole Region. Four specific objectives guided this aim: one, exploring the challenges pregnant women encounter when accessing state maternal facilities; two, exploring the bodily and physical experience of waiting on the delivery of public health care services; three, exploring the vulnerability in waiting through the lens of pregnant women; and four, exploring the relationship of government interventions through waiting. The findings of this research demonstrate that public maternal health care is accessible for most women based on the effectiveness of government policies and interventions. However, medical personnel experience constraints that restrict access to quality care. The challenges associated with waiting and medical personnel continue to impact the perception that women create of the delivery of public health care services. Addressing the challenge of waiting requires policies and interventions to align with expanding human resources to deliver the highest quality services.